(untitled) (Delta Medical College Journal, 2024)
Background: Spleen is a haemo-lymph organ and belongs to the reticuloendothelial system of human body. The spleen plays a central role in the pathophysiology of several potentially severe diseases and increasing application of sophisticated procedures in radiology and surgery requires a profound knowledge of the gross and histomorphological aspects of the human spleen and also its vascular pattern. Objective: The present study was carried out to minimize the dependency on foreign standards and to identify the morphological changes with a view to establish a data related to spleen of Bangladeshi people. Materials and method: A cross sectional descriptive study was performed on 65 postmortem human spleen (34 of male and 31 of female) by purposive sampling technique and their different shapes were noted. Dissection was performed according to standard autopsy techniques. Results: There were variations of the shapes of the spleen, 2 were found disc shaped (3.07%), 2 were irregular (3.07%), 21 were oval (32.30%), 7 were tetrahedral (10.76%), 8 were triangular (10.76%) and 26 were wedge shaped (40.0%). Conclusion: From the present study, it was concluded that six types of shapes of spleen were observed, common shapes were wedge and oval shape, with less frequent occurrence of triangular and tetrahedral and few were disc and irregular. The finding of the present study will be of fundamental importance to medical teaching and also to clinicians. Delta Med Col J. Jan 2021;9(1):33-36